Participação dos receptores adrenérgicos Alfa2 do núcleo parabraquial lateral no controle da ingestão de sódio - Andrade, Carina Aparecida Fabrício de (2006)
Water and NaCl intake is strongly inhibited by the activation of α2-adrenergic receptors with clonidine or moxonidine (α2-adrenergic/imidazoline agonists) injected peripherally or into the forebrain and by serotonin and cholecystokinin into the lateral parabrachial nucleus (LPBN), a pontine structure. Serotonergic and cathecolaminergic neurons are present in the projection from AP/NTS to the LPBN and the presence of α2- adrenergic sites in the LPBN has been shown. The aim of the present study was to investigate the possible involvement of α2-adrenergic receptors of the LPBN in the control of water and 0.3 M NaCl intake induced by the treatment with subcutaneous furosemide (FURO, 10 mg/kg of body weight) + captopril (CAP, 5 mg/kg of body weight) and also during cellular dehydration induced by intragastric 2 M NaCl load (2 ml). In addition, the possible interaction between α2-adrenergic receptors and serotoninergic, GABAergic or opioidergic mechanisms in the LPBN to control of water and 0.3 M NaCl intake was also investigated. Male Holtzman rats with cannulas implanted bilaterally in the LPBN were used. Contrary to forebrain injections, bilateral LPBN injections of moxonidine produced a strong and surprising increase in FURO + CAP-induced 0.3 M NaCl intake and a small increase in water intake, without change mean arterial pressure and heart rate or FURO + CAP-induced c-fos expression in forebrain areas related to the control of fluid-electrolyte balance. Prior injections of RX 821002 (α2-adrenergic antagonist, 10 and 20 nmol/0.2 µl) abolished the effect of moxonidine (0.5 nmol) on 0.3 M NaCl intake. Bilateral injections of moxonidine (0.5 nmol/0.2 µl) into the LPBN also induced a strong ingestion of 0.3 M NaCl intake, without changing water intake in rats with increased plasma osmolarity. However, moxonidine into the LPBN in satiated rats not treated with 2 M NaCl produced no change on 0.3 M NaCl intake. The activation of the LPBN α2-adrenoceptors inhibited the LPBN serotonergic inhibitory mechanism involved in the control of water and NaCl intake, and the increase in FURO+CAP-induced sodium intake produced by the activation of the α2-adrenergic receptors in the LPBN was partially dependent on GABAergic or opioidergic mechanisms in the LPBN. In rats submitted to the taste reactivity test to oral infusions of a 0.3 M sodium solution, the blockage serotonergic receptors into the LPBN enhanced positive hedonic taste reactivity patterns. In conclusion, previous and present results indicate opposite roles for α2-adrenergic receptors in the control of sodium and water intake according to their distribution in the rat brain. The α2-adrenergic activation into the LPBN produces a potent increase in hypertonic sodium intake during extracellular and cellular dehydration. These effects of α2-adrenergic activation into the LPBN is possibly due to the inhibitory serotoninergic mechanisms blockage into the LPBN and at least part of these effects is also dependent of an interaction with GABAergic and opioidergic mechanisms into the same area. Finally, the blockade of serotonergic receptors in the LPBN can enhance sodium palatability thus contributing to the increase in sodium intake during cell dehydration.